Out of the wild: the wild (and often weedy) roots of our crops. Issue 4 (5th April 2022) - Särkinen, Tiina; Gagnon, Edeline; Knapp, Sandra
Abstract : This article is a Commentary on Muñoz‐Rodríguez et al . (2022), 234 : 1185–1194 .